The Effect of Within-Sector, Upstream and Downstream Energy Taxes on Innovation and Productivity - Chiara Franco; Giovanni Marin (Fondazione Eni Enrico Mattei (FEEM), 2013)
The aim of the paper is to investigate the effect of environmental stringency on innovation and productivity using a cross-country panel made up of 7 European countries for 13 manufacturing sectors over the years 2001-2007. This research topic goes under the heading of Porter Hypothesis (PH) of which different versions have been tested. We take into consideration both the strong and the weak versions while adding some peculiarities to the analysis. Firstly, we assess the role played by a specific environmental regulation, that is energy taxes, that have rarely been empirically tested as factors that can favour PH hypothesis to be verified. Secondly, we do not consider, within the same framework, only the effect of energy taxes in the same sector (within-sector), but also the role played by energy taxes in upstream and downstream sectors in terms of input-output relationship. Thirdly, we test these relationships also “indirectly” by verifying whether innovation can be one of the channels through which higher sectoral productivity can be reached. The main findings suggest that downstream stringency is the most relevant driver for innovation and that most of the effect of regulation on productivity is direct, while the part of the effect mediated by induced innovation is not statistically significant.
Keywords: L6; O13; Q55; 330; Energy Taxes; Porter Hypothesis; Upstream; Downstream